Web application design for credit evaluation: proposal in a financial institution - Cano Lengua, Miguel Ángel (2023)
This article highlights the importance of implementing technological solutions in financial institutions to adequately manage credit risk since the main problem of financial organizations currently lies in the credit process. The objective of this research work is to design a web application to control the granting of credits in order to reduce the high-risk portfolio of the financial institution. The project was carried out by applying the scrum methodology, starting with the analysis for which information was collected through meetings and the use of tools such as questionnaires to identify then the necessary variables that will allow the selection of the ideal neural network algorithm that will allow us to improve the control of credit granting. Finally, the application prototypes are presented, so the respective measurement is carried out, for which the survey is divided into 4 dimensions.